A study of temperature dependent local atomic displacements in a Ba(Fe1−xCox)2As2 superconductor. Issue 13 (11th March 2016) - Hacisalihoglu, M. Y.; Paris, E.; Joseph, B.; Simonelli, L.; Sato, T. J.; Mizokawa, T.; Saini, N. L.
Abstract : Fe–Fe atomic correlations, determined by polarized EXAFS on single crystal samples of optimally doped Ba(Fe1− x Co x )2 As2 superconductor showing a decrease across the transition temperature T c . Abstract : We have studied the local structure of a Ba(Fe1− x Co x )2 As2 superconductor using temperature dependent extended X-ray absorption fine structure (EXAFS) measurements. Polarized EXAFS at the Fe K-edge on an optimally doped ( x = 0.06) single crystal has permitted us to determine atomic displacements across the superconducting transition temperature ( T c ). The Fe–As bondlength hardly shows any change with temperature; however, the Fe–Fe sublattice reveals a sharp anomaly across T c, indicated by a significant drop in mean square relative displacements, similar to the one known for cuprates and A15-type superconductors. We have also found a large atomic disorder around the substituted Co, revealed by polarized Co K-edge EXAFS measurements. The Co–Fe/Co bonds are more flexible than the Fe–Fe bonds with the As-height in Co-containing tetrahedra being larger than the one in FeAs4 . The results suggest that the local Fe–Fe bondlength fluctuations and the atomic disorder in this sub-lattice should have some important role in the superconductivity of Ba(Fe1− x Co x )2 As2 pnictides.